2006
DOI: 10.1007/s00114-006-0176-0
|View full text |Cite
|
Sign up to set email alerts
|

Floral odor learning within the hive affects honeybees’ foraging decisions

Abstract: Honeybees learn odor cues quickly and efficiently when visiting rewarding flowers. Memorization of these cues facilitates the localization and recognition of food sources during foraging flights. Bees can also use information gained inside the hive during social interactions with successful foragers. An important information cue that can be learned during these interactions is food odor. However, little is known about how floral odors learned in the hive affect later decisions of foragers in the field. We stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 16 publications
4
50
0
1
Order By: Relevance
“…Although it is impossible to distinguish between colony-level and temporal effects because individuals were not collected from the three colonies concurrently, if the increase in spontaneous responses is temporal (intraseasonal) it is consistent with other studies (Erber et al, 1980;Harris and Woodring, 1992). This variation may be a result of a plethora of things including increased exposure during foraging to volatile geraniol produced by flowers (Gerber et al, 1996;Arenas et al, 2007), or fluctuations in octopamine levels (Harris and Woodring, 1992). Each of these may also explain apparent satiation observed here but not in Frost et al (Frost et al, 2011).…”
Section: Spontaneous and Delayed Responsessupporting
confidence: 82%
“…Although it is impossible to distinguish between colony-level and temporal effects because individuals were not collected from the three colonies concurrently, if the increase in spontaneous responses is temporal (intraseasonal) it is consistent with other studies (Erber et al, 1980;Harris and Woodring, 1992). This variation may be a result of a plethora of things including increased exposure during foraging to volatile geraniol produced by flowers (Gerber et al, 1996;Arenas et al, 2007), or fluctuations in octopamine levels (Harris and Woodring, 1992). Each of these may also explain apparent satiation observed here but not in Frost et al (Frost et al, 2011).…”
Section: Spontaneous and Delayed Responsessupporting
confidence: 82%
“…In this case, harnessed bees could not have learned to approach the odour during conditioning, thus showing that transfer between situations did indeed exist. The possible natural function of this transfer ability may be related to the observation that bees do indeed learn to associate odours and nectar reward within the hive during trophallaxis with returning foragers (Farina et al, 2005;Gil and De Marco, 2005), and subsequently choose the odour learnt within the hive in a foraging context (von Frisch, 1946;Arenas et al, 2007). Most importantly, these experiments also showed that after the formation of an odour-sucrose association, the learnt odour had acquired a positive/attractive nature for the animal.…”
Section: Discussionmentioning
confidence: 95%
“…Immediately after landings experimental bees were captured and eliminated in order not to be double counted. Testing events lasted 10 min and were performed four times a day after the training feeder was removed (Arenas et al, 2007). Testing feeders were scented by two glass Petri dishes (1 cm high, 15 cm in diameter) containing a filter paper disk (55 mm in diameter) soaked with a pure odor (50 µL pure odorant) placed below each feeder (Arenas et al, 2007).…”
Section: Testing Proceduresmentioning
confidence: 99%
“…Prior experiences with food odors have also been studied in a foraging context after feeding the entire colony with scented sugar solution (Arenas et al, 2007). After this treatment a preference for a prior circulated food scent was observed in an operant context (i.e.…”
Section: Introductionmentioning
confidence: 99%